The increasing role of career guidance at the turn of the centuries - Jenschke, Bernhard (1999)
At the beginning this paper sketches trends of the rapid changes of nearly all life issues, especially in society, work behaviours, labour environment and demands for adjustment under new social values. As main factors which influence worldwide the economic development and the labour market are elaborated the globalization and liberalization process and the labour market aspects of feminization, ageing labour force, migration, unemployment as a global phenomenon and general changes in labour demand by occupations and skill level. A well-developed and highly qualified career guidance service is seen as one of the most effective instruments in solving these problems which are raised by the described developements. The personal and psychological effects of uncertainty and dislocation of people and the new requirements of the expected qualification standard make career guidance an important cornerstone to cope with these social aspects. Thus, the nature and structure of guidance and counselling are described under the new challenges. The international co-operation in the guidance sector has accompanied this process in delivering two important documents. The Mission Statement and the Ethical Standards of IAEVG, adopted by the General Assembly of IAEVG in 1995, show in what direction guidance services